2007
DOI: 10.1002/jbm.a.31461
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of bio‐compatibility via specific interactions in polyesters modified with a bio‐resourceful macromolecular ester containing polyphenol groups

Abstract: Specific interactions and miscibility are demonstrated in a series of binary miscible blend comprising of bio-compatible/biodegradable polyesters, such as poly(epsilon-caprolactone) (PCL), poly(ethylene adipate) (PEA), or poly (butylene adipate) (PBA), and a macromolecular ester with polyphenol groups, tannic acid (TA). Thermal analysis and infrared spectroscopy were used for proving existence of favorable interactions, and polarized-light optical microscopy was used for characterizing the changes in crystal g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 55 publications
2
26
0
Order By: Relevance
“…[19] Expectedly, H-bonding may also be present between PESu (with carbonyl C¼O) and TA (with hydroxyl ÀOH). Evidence of strong hydrogen bonding between TA and PESu was adequately proven by analyzing FT-IR spectra for the TA/ PESu blends, which are not shown here for brevity.…”
Section: Single Crystal Dendritesmentioning
confidence: 99%
See 1 more Smart Citation
“…[19] Expectedly, H-bonding may also be present between PESu (with carbonyl C¼O) and TA (with hydroxyl ÀOH). Evidence of strong hydrogen bonding between TA and PESu was adequately proven by analyzing FT-IR spectra for the TA/ PESu blends, which are not shown here for brevity.…”
Section: Single Crystal Dendritesmentioning
confidence: 99%
“…TA has been known to disrupt and ultimately destroy the ring-banded pattern in the spherulites when TA is present to interact a semicrystalline polymer, such as poly(ethylene adipate) (PEA), poly(butylene adipate) (PBA), or PCL, each of which is capable of forming ring-banded spherulites when crystallized at a suitable range of T c . [19] PESu, contrary to PEA, PBA or PCL, does not crystallize into ring-banded spherulites at all at any T c . Aim of this study was to probe effects of strongly interacting TA on the crystalline morphology of a semicrystalline polymer that exhibits no ring bands but only ringless Maltese-cross spherulites.…”
Section: Introductionmentioning
confidence: 99%
“…Woo and coworker have recently studied the specific interactions and miscibility of a series of binary miscible blend comprising of biodegradable polyesters, such as PCL, poly(ethylene adipate), poly(butylene adipate) (PBA), and TA. The appearance of a single composition‐dependent glass transition temperature indicated that TA is miscible with PCL, PBA, and PEA over the whole compositions range, respectively; moreover, fourier transform infrared spectroscopy confirmed the presence of specific intermolecular hydrogen bonding interactions between the carbonyl groups of polyesters and the phenolic hydroxyl groups of TA 16…”
Section: Introductionmentioning
confidence: 99%
“…All the four blends evaluated by the calorimetric data showed only a one‐phase behavior with a single Tg (data not shown) indicating miscibility between the protein and OSA‐modified polysaccharides as suggested in a study of synthetic polymers blends by (Hsu ). It seems that there is a high degree of hydrogen bonding interaction present in the blends that allowed the miscibility between these biopolymers, as it was previously confirmed by FTIR spectroscopy of combination between the carbonyl groups of biodegradable polyesters and the phenolic hydroxyl groups of tannic acid (Yen and others ) and phenolic resin (Kuo and others ). The lowest and highest reduction of approximately 3 °C and 7 °C in the Tg was observed for a combination of 3%‐OSA‐modified phytoglycogen/WPI and 3%‐OSA‐modified DWxRc/WPI, respectively (Figure B), which indicates that the hydrogen bonding interaction between these biopolymers is influenced by their chemistry and the conformational characteristic of the molecules.…”
Section: Resultsmentioning
confidence: 56%